Diffusion of oxygen in some binary Ti-Based alloys used as biomaterials - Grandini, Carlos Roberto [UNESP] (Trans Tech Publications, 2015)
Ti and its alloys are widely used as biomaterials. Their main properties are excellent corrosion resistance, relatively low elastic modulus, high specific strength, and good biocompatibility. The development of new Ti alloys with properties favorable for use in the human body is desired. To this end, Ti alloys with Mo, Nb, Zr, and Ta are being developed, because these elements do not cause cytotoxicity. The presence of interstitial elements (such as oxygen and nitrogen) induces strong changes in the elastic properties of the material, which leads to hardening or softening of the alloy. By means of anelastic spectroscopy, we are able to obtain information on the diffusion of these interstitial elements present in the crystalline lattice. In this paper, the effect of oxygen on the anelastic properties of some binary Ti-based alloys was analyzed with anelastic spectroscopy. The diffusion coefficients, pre-exponential factors, and activation energies were calculated for oxygen and nitrogen in these alloys.
Keywords: Diffusion; Ti Alloys; Interstitials